Pengaruh Pembagian Kerja Dan Pengawasan Terhadap Efektivitas Kerja Pegawai Pada Badan Kepegawaian Dan Pengembangan Sdm Kota Pagar Alam - Markus, Markus (Universitas Muhammadiyah Palembang, 2020)
Purpose - This study aims to determine the effect of Division of Employment on Employee Effectiveness On Employment Agency and Human Resource Development Pagar Alam Regency, the influence of Supervision on Employee Effectiveness On Employment Agency and Human Resource Development Lahat Regency, and the influence of Division of Work and Supervision on Employee Effectiveness On Employment Agency and Human Resource Development Pagar Alam District.Design/methodology - The sample in this study amounted to 45 respondents who distributed to Personnel Agency and Human Resource Development Pagar Alam District. The data analysis method used is quantitative analysis by using validity test, reliability test, normality test, multiple linear regression analysis and average difference test.Findings - Results Division of Labor has a positive and significant effect on Employee Effectiveness. It can be seen from t count> t table (3,692> 2,015). And the value of Supervision have a positive and significant effect on Employee Effectiveness. This can be seen from the value of t arithmetic> t table (2.456> 2.018). And Division of Labor and Supervision simultaneously have a positive and significant effect on Employee Effectiveness. It can be seen from the value of F arithmetic> F table (189,490> 3,23) and significance value <0,05 (0,000 <0,05) significance level (?).